Cross-Border Green Contracts: Promoting Sustainability Through Challenges, and Governance Recommendations (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article examines cross-border green contracts as an effective mechanism for global environmental governance and sustainable development. These contracts are legally binding agreements between entities from different states, aimed at jointly achieving environmental goals such as emission reduction, biodiversity conservation, and sustainable resource use. The focus is on analyzing their structure, key characteristics, implementation challenges, and successful cases from various world regions, including the European Union, Amazon, and East Africa. The study highlights the roles of stakeholders, including states, NGOs, the private sector, and local communities. Recommendations are made to strengthen legal, institutional, and financial support mechanisms. Thus, cross-border green contracts are recognized as an important tool in promoting fair and effective international environmental policy.